Artificial intelligence acceptance in services: connecting with Generation Z - Vitezić, Vanja; Perić, Marko (The Service industries journal, 2021)
This paper aims to examine willingness to accept artificial intelligence (AI) devices, focusing on the so-called Gen Z population. This study presumes that specific knowledge of a business process is important for AI adoption in hospitality services. A research model, grounded in the artificially intelligent device use acceptance (AIDUA) framework, used data collected from 786 respondents. The model was tested using PLS-SEM methodology. The modified framework was supported by Gen Z, with hedonic motivation having the greatest effect on Gen Z members' emotions and their willingness to use AI devices in hospitality. The frequency of smartphone usage played a significant moderating role between the perceived effort of AI usage and emotions. This study helps AI designers and business managers when designing and implementing AI devices in a hospitality environment. Based on this study's findings, policymakers and educational institutions can try to advance their curricula, emphasizing the importance of new technologies.